Verteilte Erstellung und Aktualisierung von Schlüsselservern in identitätsbasierten Verschlüsselungssystemen - Tezer, Alina

Unlinkable content playbacks in a multiparty DRM system - Petrlic, Ronald; Sekula, Stephan (Data and Applications Security and Privacy XXVII)
We present a solution to the problem of privacy invasion in a multiparty digital rights management scheme. (Roaming) users buy content licenses from a content provider and execute it at any nearby content distributor. Our approach, which does not need any trusted third party - in contrast to most related work on privacy-preserving DRM - is based on a re-encryption scheme that runs on any mobile Android device. Only a minor security-critical part needs to be performed on the device's smartcard which could, for instance, be a SIM card.

Towards practical privacy-preserving Digital Rights Management for Cloud Computing - Joshi, Nakul; Petrlic, Ronald (Proceedings of the 10th Annual IEEE Consumer Communications & Networking Conference (CCNC))
We propose a privacy-preserving digital rights management scheme for (future) cloud computing. Users buy software from software providers and execute it at computing centers. Our solution allows software providers to provide different license models, like execute at most n-times models. Users’ anonymity and unlinkability of actions are preserved and thus, profile building is not even possible under (a) pseudonym. Privacy protection in the honest-but-curious model is achieved by combining ring signatures with an anonymous recipient scheme.We employ secret sharing in a unique manner that allows the software provider to expose the user’s identity if the user commits fraud, e.g. by exceeding the execution limit n.

Seitenkanalresistenz paarungsbasierter Kryptographie - Otte, Oliver

Security Proofs for Pairing-Based Cryptography in the Generic Group Model - Bobolz, Jan

Securing Critical Unattended Systems with Identity Based Cryptography - A Case Study - Blömer, Johannes; Günther, Peter; Krummel, Volker (Proceedings of the 5th International Conference on Mathematical Aspects of Computer and Information Sciences (MACIS))
Unattended systems are key ingredients of various critical infrastruc-tures like networks of self service terminals or automated teller machines.For cost and efficiency reasons they should mostly run autonomously.Unattended systems are attractive and lucrative targets for various kindsof attacks, including attacks on the integrity of their components and thecommunication between components. In this paper, we propose a gen-eral cryptographic framework to protect unattended systems. We alsodemonstrate that instantiating the framework with techniques from iden-tity based cryptography is particularly well-suited to efficiently secureunattended systems.

IRIS: A Robust Information System Against Insider DoS-Attacks - Eikel, Martina; Scheideler, Christian (Proceedings of the 25th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this work we present the first scalable distributed information system,i.e., a system with low storage overhead, that is provably robust againstDenial-of-Service (DoS) attacks by a current insider. We allow acurrent insider to have complete knowledge about the information systemand to have the power to block any ε-fraction of its serversby a DoS-attack, where ε can be chosen up to a constant. The taskof the system is to serve any collection of lookup requests with at most oneper non-blocked server in an efficient way despite this attack. Previously,scalable solutions were only known for DoS-attacks of past insiders, where apast insider only has complete knowledge about some past time pointt_0 of the information system. Scheideler et al. (DISC 2007, SPAA 2009) showedthat in this case it is possible to design an information system so that anyinformation that was inserted or last updated after t_0 is safe against a DoS-attack. But their constructions would not work at all for a current insider. The key idea behindour IRIS system is to make extensive use of coding. More precisely, we presenttwo alternative distributed coding strategies with an at most logarithmicstorage overhead that can handle up to a constant fraction of blocked servers.

Identifikation und Wiederherstellung von kryptographischen Schlüsseln mit FPGAs - Riebler, Heinrich
Keywords: coldboot

Entwurf eines datenschutzgerechten Reputationssystems - Lutters, Sascha

Entwicklung und Analyse einer verteilten Speicherverwaltung für dynamische heterogene Speichersysteme - Hilleckes, Hendrik

Direct Chosen-Ciphertext Secure Attribute-Based Key Encapsulations without Random Oracles - Blömer, Johannes; Liske, Gennadij
We present a new technique to realize attribute-based encryption (ABE) schemes secure in the standard model against chosen-ciphertext attacks (CCA-secure). Our approach is to extend certain concrete chosen-plaintext secure (CPA-secure) ABE schemes to achieve more efficient constructions than the known generic constructions of CCA-secure ABE schemes. We restrict ourselves to the construction of attribute-based key encapsulation mechanisms (KEMs) and present two concrete CCA-secure schemes: a key-policy attribute-based KEM that is based on Goyal's key-policy ABE and a ciphertext-policy attribute-based KEM that is based on Waters' ciphertext-policy ABE. To achieve our goals, we use an appropriate hash function and need to extend the public parameters and the ciphertexts of the underlying CPA-secure encryption schemes only by a single group element. Moreover, we use the same hardness assumptions as the underlying CPA-secure encryption schemes.

CONE-DHT: A distributed self-stabilizing algorithm for a heterogeneous storage system - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 27th International Symposium on Distributed Computing (DISC))
We consider the problem of managing a dynamic heterogeneous storagesystem in a distributed way so that the amount of data assigned to a hostin that system is related to its capacity. Two central problems have to be solvedfor this: (1) organizing the hosts in an overlay network with low degree and diameterso that one can efficiently check the correct distribution of the data androute between any two hosts, and (2) distributing the data among the hosts so thatthe distribution respects the capacities of the hosts and can easily be adapted asthe set of hosts or their capacities change. We present distributed protocols forthese problems that are self-stabilizing and that do not need any global knowledgeabout the system such as the number of nodes or the overall capacity of thesystem. Prior to this work no solution was known satisfying these properties.

Ca-Re-Chord: A Churn Resistant Self-stabilizing Chord Overlay Network - Graffi, Kalman; Benter, Markus; Divband, Mohammad; Kniesburges, Sebastian; Koutsopoulos, Andreas (Proceedings of the Conference on Networked Systems (NetSys))
Self-stabilization is the property of a system to transfer itself regardless of the initial state into a legitimate state. Chord as a simple, decentralized and scalable distributed hash table is an ideal showcase to introduce self-stabilization for p2p overlays. In this paper, we present Re-Chord, a self-stabilizing version of Chord. We show, that the stabilization process is functional, but prone to strong churn. For that, we present Ca-Re-Chord, a churn resistant version of Re-Chord, that allows the creation of a useful DHT in any kind of graph regardless of the initial state. Simulation results attest the churn resistance and good performance of Ca-Re-Chord.

Attributbasierte Verschlüsselung mittels Gittermethoden - Mathematische Grundlagen, Verfahren und Sicherheitsbeweise - Kohn, Kathlén

A privacy-friendly Architecture for future Cloud Computing - Petrlic, Ronald; Sekula, Stephan; Sorge, Christoph (International Journal of Grid and Utility Computing)
We present a privacy-friendly architecture for a future cloud computing scenario where software licensing and software payment plays a major role. We show how digital rights management as a technical solution for software licensing can be achieved in a privacy-friendly manner. In our scenario, users who buy software from software providers and execute it at computing centres stay anonymous. At the same time, our approach guarantees that software licenses are bound to users and that their validity is checked before execution. Thus, DRM constitutes an incentive for software providers to take part in such a future cloud computing scenario. We employ a software re-encryption scheme so that computing centres are not able to build profiles of their users – not even under a pseudonym. We make sure that malicious users are unable to relay software to others.

FPGA-accelerated Key Search for Cold-Boot Attacks against AES - Riebler, Heinrich; Kenter, Tobias; Sorge, Christoph; Plessl, Christian (Proceedings of the International Conference on Field-Programmable Technology (FPT))
Cold-boot attacks exploit the fact that DRAM contents are not immediately lost when a PC is powered off. Instead the contents decay rather slowly, in particular if the DRAM chips are cooled to low temperatures. This effect opens an attack vector on cryptographic applications that keep decrypted keys in DRAM. An attacker with access to the target computer can reboot it or remove the RAM modules and quickly copy the RAM contents to non-volatile memory. By exploiting the known cryptographic structure of the cipher and layout of the key data in memory, in our application an AES key schedule with redundancy, the resulting memory image can be searched for sections that could correspond to decayed cryptographic keys; then, the attacker can attempt to reconstruct the original key. However, the runtime of these algorithms grows rapidly with increasing memory image size, error rate and complexity of the bit error model, which limits the practicability of the approach.In this work, we study how the algorithm for key search can be accelerated with custom computing machines. We present an FPGA-based architecture on a Maxeler dataflow computing system that outperforms a software implementation up to 205x, which significantly improves the practicability of cold-attacks against AES.
Keywords: coldboot

Stabilization, Safety, and Security of Distributed Systems
SSS is an international forum for researchers and practitioners in the design and development of distributed systems with self-properties: (classical) self-stabilizing, self-configuring, self-organizing, self-managing, self-repairing, self-healing, self-optimizing, self-adaptive, and self-protecting. Research in distributed systems is now at a crucialpoint in its evolution, marked by the importance of dynamic systems such as peer-to-peer networks, large-scale wireless sensor networks, mobile ad hoc networks, cloud computing, robotic networks, etc. Moreover, new applications such as grid and web services, banking and e-commerce, e-health and robotics, aerospace and avionics, automotive, industrial process control, etc. have joined the traditional applications of distributed systems. The theory of self-stabilization has been enriched in the last 30 years by high quality research contributions in the areas of algorithmic techniques, formal methodologies, model theoretic issues, and composition techniques. All these areas are essential to the understanding and maintenance of self-properties in fault-tolerant distributed systems.

Self-Organizing Particle Systems - Drees, Maximilian; Hüllmann (married name: Eikel), Martina; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Nanoparticles are getting more and more in the focus of the scientic community since the potential for the development of very small particles interacting with each other and completing medical and other tasks is getting bigger year by year. In this work we introduce a distributed local algorithm for arranging a set of nanoparticles on the discrete plane into specic geometric shapes, for instance a rectangle. The concept of a particle we use can be seen as a simple mobile robot with the following restrictions: it can only view the state of robots it is physically connected to, is anonymous, has only a constant size memory, can only move by using other particles as an anchor point on which it pulls itself alongside, and it operates in Look-Compute-Move cycles. The main result of this work is the presentation of a random distributed local algorithm which transforms any given connected set of particles into a particular geometric shape. As an example we provide a version of this algorithm for forming a rectangle with an arbitrary predened aspect ratio. To the best of our knowledge this is the rst work that considers arrangement problems for these types of robots.

Proxy Re-Encryption in a Privacy-Preserving Cloud Computing DRM Scheme - Petrlic, Ronald (Proceedings of 4th International Symposium on Cyberspace Safety and Security (CSS))
In a cloud-computing scenario where users buy software from software providers and execute it at computing centers, a digital rights management (DRM) system has to be in place to check the software licenses during each software execution. However, the exposure of users to privacy invasion in the presence of DRM systems is problematic.We come up with a concept that unites software providers' and users' demands for a secure and privacy-preserving DRM system for cloud computing. The employment of proxy re-encryption allows for a prevention of profile building (under pseudonym) of users by any party.

Privacy-Preserving DRM for Cloud Computing - Petrlic, Ronald; Sorge, Christoph (Proceedings of the 26th IEEE International Conference on Advanced Information Networking and Applications (AINA))
We come up with a digital rights management (DRM) concept for cloud computing and show how license management for software within the cloud can be achieved in a privacy-friendly manner. In our scenario, users who buy software from software providers stay anonymous. At the same time, our approach guarantees that software licenses are bound to users and their validity is checked before execution. We employ a software re-encryption scheme so that computing centers which execute users’ software are not able to build user profiles—not even under pseudonym—of their users. We combine secret sharing and homomorphic encryption. We make sure that malicious users are unable to relay software to others. DRM constitutes an incentive for software providers to take part in a future cloud computing scenario.We make this scenario more attractive for users by preserving their privacy.